Exploring Teachers’ Agency to Overcome the Challenges Post- Pandemics English Language Teaching - Wahyuningtias, Dwi Dyah; Prasetya, Willy (Universitas Teuku Umar, 2023)
Teachers in Indonesia have gone through a serious crisis of challenges over the last few years due to the COVID-19 pandemic, which has resulted in changes that occurred in the Indonesian education world after the epidemic ended. Teachers may have to rebuild their class conditions to manage their classes well and also face challenges in class conditions as they adapt to the new curriculum component. The study examines what challenges teachers face and how teacher agency is in dealing with new challenges after the pandemic period is over. Data analysis in this case explores the challenges arising from students and curricula as well as how schools can deal with those challenges. The method used in this study is descriptive qualitative that explores the characteristics of phenomena, explaining the underlying causes or mechanisms. This involves the collection and the data were analyzed by using semi-structural interview. The results show that teachers seek after the transition, teachers seek external training to enhance their skills and apply their knowledge effectively. School agencies and teachers provide adequate facilities for training, preparing teachers to create and use support applications.